Readings in the social control of industry. Selected by a Committee of "The American Economic Association". [With contribs of C.D. Edwards, E.S. Mason, M.W. Watkins a.o. With pref. by P.T. Homan] (The Blakiston Company, 1947)
With bibliogr. and index.